Implikasi Pragmatik yang Memunculkan Nuansa Humor Jokes pada Akun Twitter @Iari0a - Zahira, Zahra (KIRYOKU, 2023)
This research discusses about humor in Japanese language jokes from tweets at @Iari0a’s twitter account that written as dialogue conversation. The purpose of this research is to analyze and describe pragmatic implications that emerge humor nuance in jokes on @Iari0a’s twitter account. This research was conducted based on descriptive qualitative. The result shows that through Grice’s Cooperation Principle, it can be seen the jokes that follows the Cooperative Principle implies negative nuance for the listeners meanwhile the jokes that violates Cooperation Principle has contrary implication to what it says such as implying advice or imperative expression. The contrary between what it says and the implication from the speaker brings up the nuance of humor in jokes.